Prevalence and Associated Factors of Mental Disorders among Prisoners in Kenya - Museve, Judith Lipopai; Angira, Charles Helm Obiero; Aloka, Peter Jairo (International Journal of Health Sciences and Research, 2020)
Prisons have been consistently reported to have high prevalence of mental disorders compared to the general population. Prisons have initiated a number of reforms not only to help the prisoners become self-reliant upon release but also to alleviate the risk of mental disorder. It is necessary to regularly assess the prevalence of mental disorders to determine the effectiveness of the prison reform programs in mitigating the burden of mental disorders among prisoners. This study sought to determine the prevalence and associated factors of mental disorders among prisoners in Kenya. The research employed a mixed method study design that was cross-sectional in nature. A sample of 364 respondents was obtained using multi-stage sampling technique. Structured screening questionnaire and MINI International Neuropsychiatric Interview were used to screen inmates for common mental disorders. The collected data set was analyzed using SPSS version 22. Inferential statistics such as ANOVA was used to analyze quantitative data while qualitative data obtained was analyzed using Thematic Framework. There is a high prevalence of mental disorders among the prisoners at 63.2%. Gender and marital status were significantly associated with mental disorders among prisoners. Depression, Suicidality, PTSD, Mood Disorder with Psychotic Features and Generalized Anxiety Disorder were significantly associated with gender as shown by the at p-values: 0.045, 0.010, 0.001, 0.026 and 0.013 respectively. Married prisoners have the highest likelihood of having mental disorders (p = 0.017). The Kenya Prison Service Management need to conduct regular prison surveys with systematic screening and assessment of prisoners for mental health problems and mental wellbeing.
Keywords: Prevalence; mental disorders; prisons; Kenya